2014
DOI: 10.1038/eye.2014.81
|View full text |Cite
|
Sign up to set email alerts
|

A case of accidental retinal injury by cosmetic laser

Abstract: A 62-year-old Caucasian woman with a 12-month history of progressive paresthesias below the first lumbar level (L1) was hospitalized for rapid onset of ascending sensory impairment to the sixth thoracic level (T6), ataxia, saddle anesthesia, and diminishing central vision. Best-corrected visual acuity (BCVA) was 20/40 in the right eye and 20/400 in the left eye. Her BCVA had been 20/25 bilaterally two years prior. Color discrimination was severely diminished at 4/12 Ishihara color plates in the right and 1/12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 5 publications
(4 reference statements)
2
20
0
1
Order By: Relevance
“…Similar to our case, Chen et al [9] reported a peripheral retinal injury that occurred approximately 5 DD below the posterior pole; however, they were only able to report monitoring for 3 days following the injury because of patient loss. As our case was similar to that of Chen et al, [9] we considered changes in hemorrhaging over time and possible onset of retinal detachment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to our case, Chen et al [9] reported a peripheral retinal injury that occurred approximately 5 DD below the posterior pole; however, they were only able to report monitoring for 3 days following the injury because of patient loss. As our case was similar to that of Chen et al, [9] we considered changes in hemorrhaging over time and possible onset of retinal detachment.…”
Section: Discussionsupporting
confidence: 81%
“…[1] There have been recent reports regarding various retinal complications caused by cosmetic laser devices, most of which are limited to the retinal posterior pole. [38] Chen et al [9] reported a peripheral retinal injury that occurred 5 disc diameters (DD) below the macula; however, they limited their report to progress monitoring for 3 days following the injury, because of patient loss. We report on a case involving peripheral retinal injury caused by 1064-nm Nd:YAG: neodymium-doped yttrium aluminum garnet.…”
Section: Introductionmentioning
confidence: 99%
“…Recent and main complications described were uveitis, pupillary distortion, cataracts, visual field defects, macular hole, iris atrophy, posteriors synechiae, vitreous hemorrhage, and foveal photocoagulation . Lin et al .…”
Section: Resultsmentioning
confidence: 99%
“…The visual outcome may vary according to the location of the injury. Chen et al recently reported a retinal laser-induced burn associated with BCVA 20/20, despite the remarkable vitreous haemorrhage and retinal edema [7]. Another case report of a laser beam, however, which focused on the macula, caused a scar in the fovea with consequent central scotoma and BCVA 6/60 with no further improvement at an 18-month follow-up examination [8].…”
Section: Discussionmentioning
confidence: 99%